Many-particle approach to the image-charge effect - Tuovinen, Riku (2011)
Microscopical systems of molecules and atomic chains are studied to obtain information about quantum-transport phenomena. Both exact diagonalization method through second quantization and perturbation theory approach with Feynman diagrams are described, and then the energy spectra for the studied systems are calculated using the two methods.